The Implementation of Scientific Approach in the Teaching of Reading Narrative Text to the Tenth Grade Students (RETAIN, 2016)
The Implementation of Scientific Approach in the Teaching of Reading Narrative Text to the Tenth Grade Students Berliananda Sehatiin English Department, Languages and Arts Faculty, The State University of Surabaya Email:berlianandasehatiin@mhs.unesa.ac.id Him’mawan Adi Nugroho, S.Pd., M.Pd. English Department, Languages and Arts Faculty, The State University of Surabaya Email:himmawan_95@yahoo.co.id Abstract This study aims to describe how the implementation of scientific approach in the teaching of reading narrative text to the tenth grade students. Besides, this study also aims to describe three side findings, they are: the teacher’s reason why the teacher did not implement all stages in scientific approach; the difficulty which is faced by the teacher during the implementation of scientific approach; the effort which is done by the teacher to overcome the difficulty. Reseach design of this study is qualitative research. Data collection techique of this study is observation and interview. The result of this study showed that the teacher did not implement scientific approach in the teaching of reading maximal. The teacher just applied one stage of scientific approach. The teacher did not implement all stages of scientific approach because the time was not enough to conduct them. Furthermore, the teacher got difficulty in implementing questioning stage. In this case, the teacher tried to stimulate and build the students’ curious to propose questions by giving them some motivational and attracting questions. Keywords:Scientific Approach, Implementation of Scientific Approach, Reading Abstrak Penelitian ini bertujuan untuk mendeskripsikan bagaimana penerapan pendekatan saintifik pada pengajaran ketrampilan membawa teks naratif untuk siswa kelas XI. Selain itu, penelitian ini juga ditujukan untuk mendescripsikan tiga side finding, diantaranya: alasan guru tidak menerapkan semua tahapan yang terdapat dalam pendekatan saintifik, kesulitan yang dihadapi guru selama menerapkanpendekatan saintifik, dan usaha yang dilakukan guru untuk mengatasi kesulitan tersebut.Penelitian ini merupakan penelitian kualitatif. Data penelitian ini diambil dari kegiatan observasi dan interview. Hasil penelitian menunjukkan bahwa guru belum menerapkan pendekatan saintifik pada pengajaran keterampilan membawa secara maksimal. Guru tidak mengapikasikan semua tahapan pendekatan saintifik karena waktu yang terbatas. Kesulitan yang dihadapi guru terletak pada tahap menanya. Usaha yang dilakukan guru untuk mengatasi kesulitan adalah dengan memberikan pertanyaan yang memotivasi siswa untuk bertanya. Keywords: Pendekatan Saintifik, Penerapan Pedekatan Saintifik, Membaca